2002
DOI: 10.1161/01.cir.0000030188.50326.8d
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Three-Dimensional Magnetic Resonance Imaging of Atherosclerosis Development in Innominate Arteries of Low-Density Lipoprotein Receptor-Knockout Mice

Abstract: Background-In vivo methods to evaluate the size and composition of atherosclerotic lesions in animal models of atherosclerosis would assist in the testing of antiatherosclerotic drugs. We have developed an MRI method of detecting atherosclerotic plaque in the major vessels at the base of the heart in low-density lipoprotein (LDL) receptor-knockout (LDLR Ϫ/Ϫ ) mice on a high-fat diet. Methods and Results-Three-dimensional fast spin-echo magnetic resonance images were acquired at 7 T by use of cardiac and respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…B, A second reconstructed plane orthogonal to the first has been introduced to highlight the artery structure, which demonstrates the lesion extending in a cranial direction along only 1 side of the artery. 25 Prolonged imaging protocols of the sort described here are not feasible in vivo; therefore, we anticipate that further advances in microscopic plaque characterization will require new contrast agents. 34,35 Gadolinium-conjugated nanoparticles that are targeted to specific molecules have been used to image thrombus 36 and integrins 37 in larger animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B, A second reconstructed plane orthogonal to the first has been introduced to highlight the artery structure, which demonstrates the lesion extending in a cranial direction along only 1 side of the artery. 25 Prolonged imaging protocols of the sort described here are not feasible in vivo; therefore, we anticipate that further advances in microscopic plaque characterization will require new contrast agents. 34,35 Gadolinium-conjugated nanoparticles that are targeted to specific molecules have been used to image thrombus 36 and integrins 37 in larger animals.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) has also been shown to discriminate atherosclerotic plaque components in larger animal models including rabbits, [17][18][19] pigs, 20 and nonhuman primates. 21 In apoEϪ/Ϫ mice, MRI accurately quantifies atherosclerosis in the abdominal aorta, 22 aortic arch, 23 aortic root, 24 and brachiocephalic artery 25 in vivo. However, genetic and pharmacological interventions affect not only plaque size but also composition.…”
mentioning
confidence: 99%
“…The use of the aortic arch as donor tissue is particularly advantageous because (1) lesions form relatively faster and in a predictable manner in this location, 12 and (2) the preservation of the curvature of the implanted aortic arch provides for a clearer landmark for MRI. 11 We 13,14 and others 15,16 have shown that MRI can noninvasively detect atherosclerotic plaques in living mice. To our knowledge, the ability to measure plaque regression and differentiate plaque components in mice has not been demonstrated.…”
mentioning
confidence: 99%
“…Several groups are applying MRI techniques to mouse studies. High-resolution MRI is capable of detecting lipid-rich atherosclerotic plaques in mouse models of atherosclerosis (233)(234)(235)(236)(237). Dynamic contrast-enhanced MRI has been shown to be useful for evaluating atherosclerotic plaque activity in mice (238).…”
Section: Atherosclerosismentioning
confidence: 99%